8+5x-2x=6x

Simple and best practice solution for 8+5x-2x=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+5x-2x=6x equation:



8+5x-2x=6x
We move all terms to the left:
8+5x-2x-(6x)=0
We add all the numbers together, and all the variables
-3x+8=0
We move all terms containing x to the left, all other terms to the right
-3x=-8
x=-8/-3
x=2+2/3

See similar equations:

| 24+4x=-6x+124 | | 4^(2-3r)=16 | | 4x-2=68-2x | | 2x-4(x-2)=-4+5x-16 | | b+4/5=15 | | -2.12-x=2.18 | | 5b^2=-9 | | 3(5x-1)-2(3x+5)=0 | | 4r+12=-72 | | 10a-2=16 | | F(5)=3.14r^ | |               –7x+10=–20 | | -6p+3=-2(9p-6)-3(10-5p) | | 3q-1=2q+1 | | 2x+x=360-8x | | 2x+x=360-x | | 15+6n=45+8n | | 5(y+2)-3=52 | | (9x^2+8x)=(2x^2+3x) | | 2+4n=n-4 | | g85=1 | | (-3)+n=4 | | 18f=3 | | e+38=2 | | c2=4.6 | | 20+2x-7x=0 | | d+8=-143 | | 17+12x=12x-3 | | 2x-13=79 | | 1x=3.4x | | (2x-9)(3x+1)=0 | | ?/8x-3x=(8-?)x. |

Equations solver categories